Governance and agricultural growth: Evidence from selected developing countries - Aida Ariabod; Reza Moghaddasi; Yaaghoob Zeraatkish; Amir Mohammadi Nejad (Economic Journal of Emerging Markets, 2019)
Agriculture is a key sector for almost all developing countries. One of the factors influencing agricultural production improvement is government intervention and its important role in improving good governance indicators. This study examines the impact of governance on total agricultural output in developing nations. To address these issues, this paper estimates the panel data regression model. The data of Governance Indicators (GI) is provided by the World Bank. Findings/Originality: The main results suggest a reverse association between overall GI and agricultural growth. In addition, among the six individual GI, control of corruption has the highest impact. It implies that the governance has not addressed the problems in the agricultural sector. On the other hands, the development of agriculture sector is still mainly supported by the economic inputs. It is explained by the evidence that the inputs have positive and significant effect on the value of agricultural production.